Structure and properties of self-extinguishing rigid polyurethane foam with inorganic filler - Szymiczek, Małgorzata; Sarraj, Sara; Chomiak, Monika; Chmielnicki, Błażej; Gajlewicz, Izabela (Polimery, 2024)
The study examined the influence of selected inorganic fillers (5 and 10% by mass) on the foaming process, physicochemical properties, and structure of self-extinguishing polyurethane foam (density of approx. 35 kg/m3) obtained by reacting polyol with isocyanate (100:110). The filler used was bentonite (B), lamellar graphite (G), dendritic copper (Cu), aluminum oxide (Al2O3) and silicon carbide (SiC) and Al2O3/SiC mixture (1:1). Stereoscopic microscopy was used to determine the structure. The functional properties were examined based on density, water absorption and fire resistance. The course of the foaming reaction depends on the content, type, and physicochemical properties of the filler. The addition of bentonite increases water absorption and Al2O3 reduces flammability of the foam.